DEVELOPING STUDENTS’ WRITING SKILL IN ANALYTICAL EXPOSITION TEXT THROUGH CONTEXTUAL TEACHING AND LEARNING (CTL) - Risma Salima; Muhamad Taufik Hidayat (Institut Pendidikan Indonesia Garut, 2020)
This research is aimed to find out whether there is difference of students’ writing skill in analytical exposition text after the implementation of Contextual Teaching and Learning (CTL). The participants for this research were one class consisting of thirty students from the eleventh grade of a vocational school in Garut. It involved accounting class b which was selected by using purposive sampling. This research implemented pre-experimental design as research method. The data were obtained from English essay writing skill test involving pre-test and post-test in order to know the students’ writing skill before and after using contextual teaching and learning (CTL) approach. The result of the instruments was analyzed quantitatively using statistical analysis. It can be seen in the result of the hypothesis testing through Wilcoxon Test shows that Zcritical= 0.0000082 < significance level (α) =0.05. Therefore the alternative hypothesis of this research is accepted and null hypothesis of this research is rejected. And the normalized gain of this research is categorized as middle with average value 0.46. It means that contextual teaching and learning has significant effect to develop students’ writing skill in analytical exposition text.